Pertumbuhan dan Hasil Beberapa Varietas Jagung pada Berbagai Jarak Tanam - Yulisma, Yulisma (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
This study was aimed to determine the effect of varieties and spaces of planting on growth and yield of maize, using a split plot design with three replications. Main plots were V1 (Local), V2 (Bisma), V3 (Bisi 10) and V4 (P 21), and subplots were planting spacing, i.e. K1 (30 cm x 40 cm), K2 (40 cm x 40 cm), K3 (50 cm x 40 cm), K4 (60 cm x 40 cm), K5 (70 cm x 40 cm). Variety significantly affected on plant height at the age of 2-8 weeks after planting, whereas the total leaf area was significantly affected on the age of 2, 4 and 6 weeks after planting. Dry weight of plants was significantly affected at the age of 4 and 8 weeks after planting. Net assimilation rate was significantly affected at the age of 2-4 weeks after planting. Spacing treatments significantly affected on plant height at the age of 4, 6 and 8 weeks after planting. Grain yield increased from 1,081 kg to 5,249 kg/ha with an increase of plant spacing from 30 cm x 40 cm to 70 cm x 40 cm. Hybrid variety produced yield higher than that of open pollinated ones. The highest productivity as much as 7,994 kg/ha was obtained by hybrid P 21 with the plant spacing of 50 x 40 cm, followed by hybrid Bisi 10 (7,508 kg/ha), local variety (5,803 kg/ha), Bisma (5,345 kg/ha) with the same plant spacing of 50 cm x 40 cm.